Elementos para una tipología de los pobres asistidos en el Hospital de Caridad de Montevideo (1787-1830) - Bianchi, Diana (Revista Complutense de Historia de América, 2001)
The port of Montevideo exported the agricultural production of a highly fertile territory on the frontier disputed by Spain and Portugal. A charity hospital was founded in the city in 1787, to be managed by a secular brotherhood under a religious patron, which showed a strong influence of Spanish Enlightened thought, as well as local peculiarities. Its archives are a rich source of information on the economy, wars, ethnic composition of the population, issues of gender, and the question of slavery, revealing —from the perspective of the world of poverty— decisive aspects of the country’s history, even beyond its independence in 1830.